Multi-Trip Open Vehicle Routing Problem with Time Windows: A case study - Hashemi, Saeedeh; Salari, Majid; Ranjbar, Mohammad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
In this paper, we introduce a practical variation of the standard vehicle routing problem (VRP). The problem is a combination of the multi-trip, open and VRP with time windows. A practical application of the introduced problem is to provide service for the university professors. In the studied problem, a set of professors have to teach at a university located in another city. The goal is planning and scheduling services for professors in order to minimize the total transportation cost with a set of side constraints including the maximum travel time for each passenger. We provide two mathematical models namely, node-based and scenario-based formulations. In addition, we present a heuristic method to produce feasible scenarios for the scenario-based model. Computational results clearly indicate the effectiveness of the models by solving real size instances.